Case Report: Minimally Invasive Therapy by Transcatheter Aortic Valve Replacement and Percutaneous Intramyocardial Septal Radiofrequency Ablation for a Patient With Aortic Stenosis Combined With Hypertrophic Obstructive Cardiomyopathy: Two-Year Follow-Up Results - Li, Yijian; Feng, Yuan; Li, Xi; Zuo, Lei; Gu, Tao; Liu, Liwen; Chen, Mao (Frontiers in Cardiovascular Medicine, 2021)
With the development of minimally invasive technologies in the medical field, more and more technologies can replace surgical thoracotomy and relieve the pain of disease via minimally invasive methods. We reported a case of aortic valve stenosis combined with left ventricular outflow track obstruction treated by two minimally invasive techniques, transcatheter aortic valve replacement and transthoracic echocardiography–guided percutaneous intramyocardial septal radiofrequency ablation, and followed up for 2 years.